1000 HPK Parenting Promotion Program in Kepulauan Seribu 2018-2020: Reviewed from The Theory of Hafied Cangara Communication Strategy - Restu Rahmawati; Clara Cindy (Indonesian Association for Public Administration (IAPA), 2021)
This study aims to determine about 1000 HPK Parenting Promotion Program In Kepulauan Seribu 2018-2020: Reviewed from the Theory of Hafied Cangara Communication Strategy. This type of research is descriptive research using qualitative methods. Collecting data by conducting observations, interviews, and documentation. The communication strategy carried out by the Thousand Islands PPAPP Sub-Department refers to Hafied Cangara's theory, where in this case the communication strategy in the KIE promotion program for the Care of 1000 HPK is carried out through the first stage and then continues with planning, implementation, evaluation and reporting. The results showed that the communication strategy carried out in the 1000 HPK KIE Promotion Program was carried out through a 1000 HPK parenting training program directly face to face while practicing using the tools provided and online through webinars. In the process of implementing the program, referring to the 2018 National Priority Promotion Projection Technical Guidelines and KIE for the First 1000 Days of Life (HPK). According to Hafied Cangara's theory, the failure of the communication strategy of the 1000 HPK KIE Parenting Promotion Program for 2018- 2020 is the absence of a research process first carried out Kepulauan Seribu Sub-Department PPAPP. 1000 HPK 2018-2020. Thus, to realize the 1000 HPK Care KIE program 2018-2020 to the fullest, a process is needed before the program is implemented so that it is right on target and the community is enthusiastic about participating in the 1000 HPK Care KIE Promotion program.